Median-crown stripe variation in two ant-tanagers (Cardinalidae) - Santi Guallar; Angelina Ruiz-Sánchez; Rafael Rueda-Hernández; Peter Pyle (Ornithology Research, 2025)

Recent changes in distribution and plumage phenologies of the White-winged Tern (Chlidonias leucopterus) in the Middle East - Yosef Kiat; Peter Pyle (Journal of Ornithology, 2025)
Changes in species geographic distributions, including those of migration routes, stopover sites, and over-wintering grounds, may affect the phenology of breeding and moult. The White-winged Tern ( Chlidonias leucopterus ) is a long-distance migrant which breeds in Eurasia and winters in Africa and Australasia. This species is known in the Eastern Mediterranean and the Middle East mainly during the migration seasons although it also breeds locally in eastern Turkey and the Persian Gulf. However, in the last decade, there has been an apparent change in the winter distribution of this species, with increasing observations of individuals during December–February in the Middle East, many of them in breeding plumage. Using data collected from specimens stored at the Natural History Museum at Tring (UK), ringing data from Israel, the online database eBird, and accompanying Macaulay Library (Cornell Lab of Ornithology), we described these recent changes in the seasonal distribution and annual moult cycles. While the birds that breed in the north begin to replace their black body feathers immediately at the end of the breeding season, the birds described here displayed the black body plumage (breeding plumage) throughout the winter (December–February), a plumage pattern that is offset by seven to eight months from those of the northern-hemisphere breeding populations. This might suggest yet-to-be discovered local breeding in the Middle East in February–April. In such cases as this, we hypothesize that examination of plumage phenology may help researchers investigate the timing of as yet unknown breeding phenology.

Impact of climate change on volcanic processes: current understanding and future challenges - Thomas J. Aubry; Jamie I. Farquharson; Colin R. Rowell; Sebastian F. L. Watt; Virginie Pinel; Frances Beckett; John Fasullo; Peter O. Hopcroft; David M. Pyle; Anja Schmidt; John Staunton Sykes (Bulletin of Volcanology, 2022)
The impacts of volcanic eruptions on climate are increasingly well understood, but the mirror question of how climate changes affect volcanic systems and processes, which we term “climate-volcano impacts”, remains understudied. Accelerating research on this topic is critical in view of rapid climate change driven by anthropogenic activities. Over the last two decades, we have improved our understanding of how mass distribution on the Earth’s surface, in particular changes in ice and water distribution linked to glacial cycles, affects mantle melting, crustal magmatic processing and eruption rates. New hypotheses on the impacts of climate change on eruption processes have also emerged, including how eruption style and volcanic plume rise are affected by changing surface and atmospheric conditions, and how volcanic sulfate aerosol lifecycle, radiative forcing and climate impacts are modulated by background climate conditions. Future improvements in past climate reconstructions and current climate observations, volcanic eruption records and volcano monitoring, and numerical models all have a role in advancing our understanding of climate-volcano impacts. Important mechanisms remain to be explored, such as how changes in atmospheric circulation and precipitation will affect the volcanic ash life cycle. Fostering a holistic and interdisciplinary approach to climate-volcano impacts is critical to gain a full picture of how ongoing climate changes may affect the environmental and societal impacts of volcanic activity.

Towards a global list of accepted species V. The devil is in the detail - Richard L. Pyle; Saroj K. Barik; Les Christidis; Stijn Conix; Mark John Costello; Peter Paul van Dijk; Stephen T. Garnett; Donald Hobern; Paul M. Kirk; Aaron M. Lien; Thomas M. Orrell; David Remsen; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species II. Consequences of inadequate taxonomic list governance - Scott A. Thomson; Kevin Thiele; Stijn Conix; Les Christidis; Mark John Costello; Donald Hobern; Svetlana Nikolaeva; Richard L. Pyle; Peter Paul van Dijk; Haylee Weaver; Frank E. Zachos; Zhi-Qiang Zhang; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species IV: Overcoming fragmentation in the governance of taxonomic lists - Aaron M. Lien; Stijn Conix; Frank E. Zachos; Les Christidis; Peter Paul van Dijk; Olaf S. Bánki; Saroj K. Barik; John S. Buckeridge; Mark John Costello; Donald Hobern; Narelle Montgomery; Svetlana Nikolaeva; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species III. Independence and stakeholder inclusion - Stijn Conix; Stephen T. Garnett; Kevin R. Thiele; Les Christidis; Peter Paul van Dijk; Olaf S. Bánki; Saroj K. Barik; John S. Buckeridge; Mark J. Costello; Donald Hobern; Paul M. Kirk; Aaron Lien; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species I. Why taxonomists sometimes disagree, and why this matters - Kevin R. Thiele; Stijn Conix; Richard L. Pyle; Saroj K. Barik; Les Christidis; Mark John Costello; Peter Paul van Dijk; Paul Kirk; Aaron Lien; Scott A. Thomson; Frank E. Zachos; Zhi-Qiang Zhang; et al. (Organisms Diversity & Evolution, 2021)

Preformative molt in Neotropical Cardinalidae - Santi Guallar; Rafael Rueda-Hernández; Peter Pyle (Ornithology Research, 2020)

Migration and habitat of white sharks (Carcharodon carcharias) in the eastern Pacific Ocean - Kevin C. Weng; Andre M. Boustany; Peter Pyle; Scot D. Anderson; Adam Brown; Barbara A. Block (Marine Biology, 2007)

Influences of the El Niño/Southern Oscillation and the North Atlantic Oscillation on avian productivity in forests of the Pacific Northwest of North America - M. Philip Nott; David F. Desante; Rodney B. Siegel; Peter Pyle (Global Ecology and Biogeography, 2002)
To model the effects of global climate phenomena on avian population dynamics, we must identify and quantify the spatial and temporal relationships between climate, weather and bird populations. Previous studies show that in Europe, the North Atlantic Oscillation (NAO) influences winter and spring weather that in turn affects resident and migratory landbird species. Similarly, in North America, the El Niño/Southern Oscillation (ENSO) of the Pacific Ocean reportedly drives weather patterns that affect prey availability and population dynamics of landbird species which winter in the Caribbean. Here we show that ENSO‐ and NAO‐induced seasonal weather conditions differentially affect neotropical‐ and temperate‐wintering landbird species that breed in Pacific North‐west forests of North America. For neotropical species wintering in western Mexico, El Niño conditions correlate with cooler, wetter conditions prior to spring migration, and with high reproductive success the following summer. For temperate wintering species, springtime NAO indices correlate strongly with levels of forest defoliation by the larvae of two moth species and also with annual reproductive success, especially among species known to prey upon those larvae. Generalized linear models incorporating NAO indices and ENSO precipitation indices explain 50–90% of the annual variation in productivity reported for 10 landbird species. These results represent an important step towards spatially explicit modelling of avian population dynamics at regional scales.

HISTORICAL AND RECENT COLONIZATION OF THE SOUTH FARALLON ISLANDS, CALIFORNIA, BY NORTHERN FUR SEALS ( CALLORHINUS URSINUS ) - Peter Pyle; Douglas J. Long; Jacqueline Schonewald; Robert E. Jones; Jan Roletto (Marine Mammal Science, 2001)

PREDATION ON A WHITE SHARK ( CARCHARODON CARCHARIAS ) BY A KILLER WHALE ( ORCINUS ORCA ) AND A POSSIBLE CASE OF COMPETITIVE DISPLACEMENT - Peter Pyle; Mary Jane Schramm; Carol Keiper; Scot D. Anderson (Marine Mammal Science, 1999)

Apex marine predator declines ninety percent in association with changing oceanic climate - RICHARD VEIT; JOHN MCGOWAN; DAVID AINLEY; TERENCE WAHL; PETER PYLE (Global Change Biology, 1997)
Three time series of pelagic bird abundance collected in disparate portions of the California Current reveal a 90% decline in Sooty Shearwater (Puffinus griseus) abundance between 1987 and 1994. This decline is negatively correlated with a concurrent rise in sea‐surface temperatures; Sooty Shearwaters have declined while sea temperatures have risen. There is a nine‐month lag in the response by shearwaters to changing temperatures. The geographical scale of our study demonstrates that the decline of Sooty Shearwaters is not a localized phenomenon, nor can it be ascribed to a short‐term distributional shift. The Sooty Shearwater is the numerically dominant species of the California Current System (CCS) in summer (austral winter), with an estimated population in the late 1970s of 5 million individuals. If the observed warming of the waters of the California Current System is an irreversible manifestation of a changing global climate, then the impact upon Sooty Shearwater populations seems likely to be profound.